Synthesis and characterisation of plant-based scaffolds for cultured meat - Tan, Si Xian (Nanyang Technological University, 2022)
Cultured meat is an up-and-coming industry due to food shortage concerns globally. With this, an increase in research for scaffolding methods has been triggered to ensure the viability of the growth of cultured meat. To ensure a more sustainable food production, plant-based scaffolds are preferred in the development of cultured meat. In this project, an alginate-based hydrogel is synthesized as the scaffold. Various characterisation techniques such as fiber alignment, rheological properties and fiber diameter will be done to ensure the viability of the hydrogel. Fiber alignment and diameter characterisation will be done via the FFT analaysis. It will reflect the likelihood of cells seeding and aligning themselves to proliferate from the results obtained. Rheological characterisation will be done on the hydrogel to obtain its viscosity profile, shear stress, storage modulus and loss modulus. It will reflect the viscoelastic properties of the hydrogel and determine its suitability as a scaffold. Based on the findings, the characterisation techniques has showed promise for the alginate-based hydrogel synthesized to function as a scaffold. However, more work is needed to ensure a more comprehensive research and results to fully support the hydrogel as a viable solution.